REAKTUALISASI KONSEP TRI PUSAT PENDIDIKAN KI HAJAR DEWANTARA DALAM PERSPEKTIF PENDIDIKAN ISLAM BAGI GENERASI MILENIAL - Sukarman Sukarman (Universitas Wahid Hasyim Semarang, 2017)
AbstractThis paper is a study of thought that tried to re-actualize an educational concept of one of Indonesia's national education maestro, Ki Hajar Dewantara namely the concept of three education center. The author seeks the intersection between the concept of three education center with the concept of Islamic education. The hope is to find the relevance of the concept of three educational center with the concept of Islamic education will be a solution for the achievement of educational goals for millennial generation in the era of globalization with all its complexity. The author wants to re-awaken the awareness of the role of education from the perspective of the concept of three education center and islamic education.Keywords: re-actualization, education center, millennial generation AbstrakTulisan ini merupakan sebuah kajian pemikiran yang berusaha mengaktualisasikan kembali sebuah konsep pendidikan dari salah seorang maestro pendidikan Nasional Indonesia, Ki Hajar Dewantara yakni konsep tri pusat pendidikan. Penulis mencari titik temu anatara konsep tri pusat pendidikan dengan konsep pendidikan Islam. Harapannya adalah dengan menemukan relevansi dari konsep tri pusat pendidikan dengan konsep pendidikan Islam akan dapat menjadi solusi bagi tercapainya tujuan pendidikan bagi generasi milenial di era globalisasi dengan segala kompleksitasnya. Penulis ingin menggugah kembali kesadaran tentang peran pendidikan dari perspektif konsep tri pusat pendidikan dan pendidikan Islam.Kata-kata kunci : reaktualisasi, pusat pendidikan, generasi milenial